KERENGGANGAN SOSIAL JAMAAH MAJELIS TAFSIR AL-QUR’AN (MTA) DENGAN WARGA DUSUN KUNANG, BAYAT, KLATEN - Iffah, Izzatun (Jurnal Sosiologi Agama, 2017)
This paper would like to lift the social phenomenon in a society that has a different understanding of related social movements that based on the teachings of the Islamic religion. The rise of the Islamic movement-gerkan certainly has the characteristic of each though their main goal is the same to improve the situation of the Muslims, this difference can undoubtedly gave rise to conflict between groups. Assembly Tafir Qur'an (MTA) is one of the Islamic movement that aims to restore the Muslims in accordance with the Qur'an and Hadith. The birth of the MTA with all his teachings amongst the people had given the huge impact, the religious doctrine that does not comply with the Community poses a variety of problems. The social tension among worshipers MTA hamlet with Village communities in addition to the Glow caused by different religious doctrine there is also social jealousy because of the proximity of the Government apparatus with MTA Worshipers Village which is considered more powerful than the village officials so that more free in the conduct. However there are positive influences arising out of such kerenggangan good for the MTA nor the people themselves and present the relationships established between the MTA and the general nature of the symbiosis komensalisme. Keywords: Social Tensions, The Tafsir Al-Qur'an, Social Movements